Proceedings of the International Scientific and Practical Conference “Digital Agriculture - Development Strategy” (ISPC 2019) 2019
DOI: 10.2991/ispc-19.2019.102
|View full text |Cite
|
Sign up to set email alerts
|

Innovative technology of natural raw materials processing and biologically active complexes with systemic effect development

Abstract: The article deals with the issues of digitization in the production of specialized products based on natural raw materials of plant and animal origin, including biologically active supplements. Taking into account agriculture and food industry digitization, an innovative technology has been developed for processing a new specialized dietary supplement for the body metabolism multifactorial support. Innovative production technology ensures high safety of biologically active components due to liposomalization. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The manufacturing technology of the encapsulated food supplement was developed. It has the following stages: raw-material preparing; mixture for encapsulation preparing; raw-material sieving and blending; encapsulating and sorting capsules by their appearance; and packing, packaging and labeling [ 12 , 13 , 14 , 15 , 19 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The manufacturing technology of the encapsulated food supplement was developed. It has the following stages: raw-material preparing; mixture for encapsulation preparing; raw-material sieving and blending; encapsulating and sorting capsules by their appearance; and packing, packaging and labeling [ 12 , 13 , 14 , 15 , 19 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…In addition to pharmaceutical-drug development, it has become necessary to create new anti-atherosclerotic medicines of natural origin, including biologically active food supplements with a multicomponent composition, which can act at various stages of the disease pathogenesis. This approach will promote diet therapy as part of combination therapy and improve preventive measures for people who do not show a clinical manifestation of the disease [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The influence of an increased intake of macro-and micro-nutrients when training was studied [1,2] and international practices were compared [3]. Foods of plant, animal, or mineral origin with documented beneficial effects have been used to boost metabolism and body functions, and prevent and treat infectious and non-infectious diseases [4][5][6][7][8][9][10][11][12]. Existing research conducted by Russian scientists demonstrated that antler products, including pantohematogen, can be successfully added to the diets of professional athletes to respond to their nutritional needs during training, competition, and recovery periods [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…When the amount of food consumed is increased, the calorie content of the diet grows, which, in turn, leads to overweight and obesity and causes different diseases of civilization like cardiovascular and oncological diseases, etc. [2,[5][6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%